Effect of particle size on the physical properties of activated palm kernel shell for supercapacitor application - Ayinla, R.T. (Trans Tech Publications Ltd, 2020)
The advantages of palm kernel shell (PKS) as a renewable and sustainable material for activated carbon production have been explored for various applications such as water treatment, pollutant, pesticide, and heavy metal adsorption. However, the full promises of this material for energy storage devices have not been duly studied. In this research, PKS is physically activated and the effect of particle size on the physical characteristics of the activated char was investigated. Pellet (3 mm), granules (0.4 mm), and powder (0.0075 mm) are the sizes considered in the experiment. The surface morphology, surface area, porosity and functional group at different sized was analyzed. Finally, a suitable particle size was recommended for the electrode material of supercapacitor based on the physical characteristics of the activated carbon. Â© 2020 Trans Tech Publications Ltd, Switzerland.